ANTECEDENTS OF ENTREPRENEURIAL INTENTION AMONG MACEDONIAN YOUTH: A QUALITATIVE APPROACH - Zabijakin chatleska, Vesna; Cacanoska, Ruzica; Lazarevski, Pande (KNOWLEDGE International Journal Scientific Papers, 2017)
This paper examines antecedents of entrepreneurial intention among young population in Macedonia. Research framework is based on the Entrepreneurial Intention Model which relies on the Theory of Planed Behavior and suggested that decision about creation of a new venture is determined by certain motivational factors which are considered as antecedents of intention. In order to gain a deeper understanding of the relationship between these factors and entrepreneurial intentions, a qualitative method was applied. Using semi-structured interview, research data were collected from a purposive sample of 30 young persons aged 15 to 29 years in Macedonia. The sample stratification was done by gender, place of residence, age, educational level, employment status and ethnicity. The results reveal that young persons whose parents are entrepreneurs have subjective norms and attitudes that favor their personal entrepreneurial intentions. At the same time, they perceived negative normative believes of the referent community regarding the decision to become an entrepreneur. Also, the findings indicate that positive personal attitude towards engaging in entrepreneurial activity is driven by the aspiration to functional independence, preferences for freedom of action and expression, and, above all, it is strongly motivated by profit. Moreover, the attraction of being self-employed is affected by a desire for the successful fulfillment of professional and business goals. In regard to perceived behavioral control and the sense of capacity to fulfill entrepreneurship behavior, respondents expressed believe in their capabilities, such as: strong self-esteem, perception of high personal skills, responsibility, persistence, and ability to manage business processes.
Keywords: Entrepreneurial intention, subjective norms, personal attitudes, perceived behavioral control, Macedonian youth, qualitative study